Residential Areas for Households without Cars: The Scope for Neighbourhood Mobility Management in Scandinavian Cities - Scheurer, Jan (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
Ecological housing initiatives have proliferated throughout Scandinavia over the past two decades and fostered groundbreaking innovation in the fields of resource efficiency and the reinvigoration of communities in local areas. The travel patterns of residents in such projects, however, remain largely outside the target and the influence of the policy context, and thus constitute an unpredictable ’wildcard’ with the potential to seriously jeopardise the sustainability performance even of an otherwise highly innovative neighbourhood. To overcome such shortfalls, recent experiments in some European cities have attempted to incorporate mobility management components into the concepts of new residential developments. These include restricted or demand-responsive parking provision, on-site car sharing, rent and mobility service packages, and specific designs for live-work arrangements and/or functional integration on a neighbourhood level. Some of these carfree or car-reduced neighbourhoods have now been completed and inhabited for several years. Their history, leading up to a location-specific mobility concept in each case, and their experience with practical implementation and user compliance now allow to provide a critical review of success and failure in this field, and to draw conclusions on how similar approaches may be applied in Scandinavian cities.